Pomurje’s traffic acessibility evaluation based on road network analysis - Ivajnšič, Danijel; Novak, Tjaša (Journal for Geography, 2017)
Traffic accessibility is one of the key factors of economic development of a given area. Proper transport infrastructure development based on adequate transport policy should provide favorable conditions for traffic flow and safety and reduce its negative environmental impacts. This study discusses the traffic accessibility issues to health, care and educational institutions and to electric filling stations of the statistical region Pomurje. The main purpose of this spatial analysis is to determine the traffic accessibility of all municipalities within the study area to the selected institutions within a certain time interval (from 5 to 15 minutes), if the route is carried out with a motor vehicle or a bicycle. The Goričko area stands out with the lowest values of traffic accessibility to selected points of interest. Simultaneously, municipalities within the Murska ravan have the best traffic accessibility to the selected institutions, since the frequency of these is the highest in the nearby regional center Murska Sobota.